1975
DOI: 10.1021/bi00682a028
|View full text |Cite
|
Sign up to set email alerts
|

Mercurated polynucleotides. New probes for hybridization and selective polymer fractionation

Abstract: Polynucleotides containing covalently bound mercury atoms have been prepared by chemical or enzymatic syntheses and some of their physical and biochemical properties studied. The mercury substituents do not appear to alter significantly normal polynucleotide structure. Mercurated polymers function efficiently as templates for nucleic acid polymerases, they are fully susceptible to degradation by standard nucleases, and their denaturation and reannealing properties resemble those of the corresponding nonmercura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(64 citation statements)
references
References 29 publications
2
61
1
Order By: Relevance
“…This RNA, transcribed in vivo, is clearly a potential competitor with any in vitro transcript and is usually present in excess [4]. The facility with which UTP can be mercurated and the apparent lack of effect of this derivative on the utilisation of this nucleoside triphosphate as a substrate for RNA synthesis and on the properties of polymers containing it [5,6], suggested a method by which RNA synthesised in vitro could be resolved from any endogenous material. The following results confirm that the purified eucaryotic form A RNA polymerase will utilise Hg-UTP as a substrate analogue.…”
Section: Hg-utpmentioning
confidence: 99%
See 2 more Smart Citations
“…This RNA, transcribed in vivo, is clearly a potential competitor with any in vitro transcript and is usually present in excess [4]. The facility with which UTP can be mercurated and the apparent lack of effect of this derivative on the utilisation of this nucleoside triphosphate as a substrate for RNA synthesis and on the properties of polymers containing it [5,6], suggested a method by which RNA synthesised in vitro could be resolved from any endogenous material. The following results confirm that the purified eucaryotic form A RNA polymerase will utilise Hg-UTP as a substrate analogue.…”
Section: Hg-utpmentioning
confidence: 99%
“…The RNA products synthesised by the endogenous nucleolar form A RNA polymerase in the presence of Hg-UTP are indistinguishable from those made with UTP and they may be used in hybridisation studies after demercuration. 6 B was from Pharmacia (Uppsala, Sweden). Hg-UTP was prepared by Mr John Jenkins in this laboratory, using the method described by Dale et al [5] and, by analysis on sulphydryl-Sepharose, was shown to be free of unmercurat-ed UTP.…”
Section: Hg-utpmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization to radiolabeled cDNA would not be a suitable detection method because it does not distinguish in vitro synthesized from preexisting mRNA molecules. To overcome these difficulties, we used two different approaches, both exploiting the affinity of mercurated polynucleotides for sulfhydrylagarose (SH-agarose) (9,10). Using either method we could show that ovalbumin mRNA sequences have been synthesized by RNA polymerase B in a highly selective manner in isolated hen oviduct nuclei.…”
mentioning
confidence: 99%
“…For efficient binding of mercurated polynucleotides to SH-containing sorbents, one mercury atom/100 -200 nucleotides is sufficient [7]. Hence, for isolation of mercurated tRNAs by means of such sorbents, one mercury atom/tRNA molecule is adequate.…”
Section: Resultsmentioning
confidence: 99%